Mutations in TBX18 Cause Dominant Urinary Tract Malformations via Transcriptional Dysregulation of Ureter Development. - Vivante, Asaf; Kleppa, Marc-Jens; Schulz, Julian; Kohl, Stefan; Sharma, Amita; Chen, Jing; Shril, Shirlee; Hwang, Daw-Yang; Weiss, Anna-Carina; Kaminski, Michael M; Shukrun, Rachel; Kemper, Markus J; et al. (Am J Hum Genet, 2015)
Congenital anomalies of the kidneys and urinary tract (CAKUT) are the most common cause of chronic kidney disease in the first three decades of life. Identification of single-gene mutations that cause CAKUT permits the first insights into related disease mechanisms. However, for most cases the underlying defect remains elusive. We identified a kindred with an autosomal-dominant form of CAKUT with predominant ureteropelvic junction obstruction. By whole exome sequencing, we identified a heterozygous truncating mutation (c.1010delG) of T-Box transcription factor 18 (TBX18) in seven affected members of the large kindred. A screen of additional families with CAKUT identified three families harboring two heterozygous TBX18 mutations (c.1570C>T and c.487A>G). TBX18 is essential for developmental specification of the ureteric mesenchyme and ureteric smooth muscle cells. We found that all three TBX18 altered proteins still dimerized with the wild-type protein but had prolonged protein half life and exhibited reduced transcriptional repression activity compared to wild-type TBX18. The p.Lys163Glu substitution altered an amino acid residue critical for TBX18-DNA interaction, resulting in impaired TBX18-DNA binding. These data indicate that dominant-negative TBX18 mutations cause human CAKUT by interference with TBX18 transcriptional repression, thus implicating ureter smooth muscle cell development in the pathogenesis of human CAKUT.
Keywords: Base Sequence; Electrophoretic Mobility Shift Assay; Exome; Gene Expression Regulation, Developmental; Genes, Dominant; HEK293 Cells; Humans; Immunohistochemistry; Immunoprecipitation; Microscopy, Fluorescence; Molecular Sequence Data; Muscle, Smooth; Mutation; Pedigree; Sequence Analysis, DNA; T-Box Domain Proteins; Ureter; Urinary Tract

Multilineage somatic activating mutations in HRAS and NRAS cause mosaic cutaneous and skeletal lesions, elevated FGF23 and hypophosphatemia. - Lim, Young H; Ovejero, Diana; Sugarman, Jeffrey S; Deklotz, Cynthia M C; Maruri, Ann; Eichenfield, Lawrence F; Kelley, Patrick K; Jüppner, Harald; Gottschalk, Michael; Tifft, Cynthia J; Gafni, Rachel I; Boyce, Alison M; et al. (Hum Mol Genet, 2014)
Pathologically elevated serum levels of fibroblast growth factor-23 (FGF23), a bone-derived hormone that regulates phosphorus homeostasis, result in renal phosphate wasting and lead to rickets or osteomalacia. Rarely, elevated serum FGF23 levels are found in association with mosaic cutaneous disorders that affect large proportions of the skin and appear in patterns corresponding to the migration of ectodermal progenitors. The cause and source of elevated serum FGF23 is unknown. In those conditions, such as epidermal and large congenital melanocytic nevi, skin lesions are variably associated with other abnormalities in the eye, brain and vasculature. The wide distribution of involved tissues and the appearance of multiple segmental skin and bone lesions suggest that these conditions result from early embryonic somatic mutations. We report five such cases with elevated serum FGF23 and bone lesions, four with large epidermal nevi and one with a giant congenital melanocytic nevus. Exome sequencing of blood and affected skin tissue identified somatic activating mutations of HRAS or NRAS in each case without recurrent secondary mutation, and we further found that the same mutation is present in dysplastic bone. Our finding of somatic activating RAS mutation in bone, the endogenous source of FGF23, provides the first evidence that elevated serum FGF23 levels, hypophosphatemia and osteomalacia are associated with pathologic Ras activation and may provide insight in the heretofore limited understanding of the regulation of FGF23.
Keywords: Adolescent; Child; Exome; Female; Fibroblast Growth Factors; Gene Expression Regulation, Developmental; GTP Phosphohydrolases; Humans; Hypophosphatemia; Male; Membrane Proteins; Mutation; Nevus; Nevus, Pigmented; Osteomalacia; Proto-Oncogene Proteins p21(ras); Sequence Analysis, DNA; Skin; Skin Neoplasms